Photoreactive CMP-sialic acids as substrates for α2,6-sialyltransferase - Mirelis, Paraskevi; Brossmer, Reinhard (Bioorganic & medicinal chemistry letters, 1995)
Chemo-enzymatic synthesis afforded a series of CMP-activated sialic acids carrying a photoreactive group at C-9 or C-5, and in part a radiolabel as well. They were found to be accepted by α2,6-sialyltransferase. - Differing amino group reactivity of novel 5,9-diamino sialic acid enabled us to attach sequentially a benzophenone photophore at C-9 and a radiolabel at C-5.
Elektronische Reproduktion der Druck-Ausgabe 29. März 2000
Gesehen am 27.06.2024